Investigating the Role of Indoleamine 2,3-Dioxygenase in Acute Myeloid Leukemia: A Systematic Review - Wells, Georgia; Kennedy, Paul T.; Dahal, Lekh N. (Frontiers in Immunology, 2021)
Background- The immunomodulatory enzyme, indoleamine 2,3-dioxygenase (IDO) facilitates tryptophan catabolism at the rate-limiting step of the kynurenine (Kyn) pathway. IDO expression and elevations in Kyn metabolites are associated with immunosuppressive tumour microenvironment including T cell proliferative arrest and generation of regulatory T cells (Tregs) which can favour tumour progression. However, the extent of the role of IDO in acute myeloid leukaemia (AML) is currently ill-defined. This study reviews the role of IDO-driven Treg function in AML and evaluates the current body of evidence implicating IDO in AML pathogenesis. Method- Studies related to IDO in AML were identified through a systematic review of PubMed and Scopus. Data extracted described sample analysis, IDO expression, IDO in prognosis, techniques used in Treg phenotypic studies, and the effect of IDO inhibitors. Results- Twenty studies were included in the systematic review. Expression of IDO was identified in a range of cells in AML, both inducible and constitutive. Seven studies indicated an association between elevated expression and poor clinical prognosis. Six studies suggested a positive correlation between IDO expression and Treg abundance, with FoxP3 being the prominent Treg phenotypic marker. Of eight studies investigating IDO inhibition, some reported reductions in Treg frequency and enhanced effector T cell proliferation. Conclusion- This review highlights that IDO expression in AML is associated with poor prognosis and measurement of IDO and its Kyn metabolites may offer utility as prospective prognostic markers. Pharmacological inhibition of IDO using novel drugs may hold promise for the treatment of AML.